Muslim Society and the Concept of Khilafat: A Comparative Analysis of Allama Iqbal and Dr. Israr Ahmed’s Intellectual Interpretations: مسلم سماج اور تصورِ خلافت : علامہ اقبالؒ اور ڈاکٹر اسرار احمد کی علمی تعبیرات کا تقابلی مطالعہ (DARYAFT, 2025)
This paper presents a comparative study of Allama Muhammad Iqbal’s and Dr. Israr Ahmed’s concepts of Khilāfa (Caliphate), examining their intellectual, philosophical, and theological perspectives on Islamic political authority. Iqbal, an early twentieth-century poet-philosopher, envisioned Khilāfa as a spiritual and socio-political ideal grounded in Qur’anic principles and the collective will of the Muslim ummah. For him, it represented moral sovereignty under divine authority while rejecting autocracy and secular nationalism. In contrast, Dr. Israr Ahmed, a late twentieth-century revivalist thinker, emphasized the practical re-establishment of Khilāfa as a religious obligation, advocating a Qur’an-centered movement aimed at political and social transformation. This study does not seek a nostalgic return to the past but rather integrates Islamic intellectual tradition with constructive modern thought to address contemporary challenges. Despite their differing approaches. Iqbal’s being visionary and philosophical, and Israr Ahmed’s organizational and prescriptive, both thinkers converge on the belief that Khilāfa is essential for Muslim unity, spiritual renewal, and the realization of divine sovereignty. The analysis highlights their shared rejection of Western secular paradigms while contrasting Iqbal’s poetic-philosophical vision with Israr Ahmed’s pragmatic call to action.Conflict of Interest: The authors declare that there are no conflicts of interest related to the research, authorship, and/or publication of this article, and that the data presented have not been fabricated or falsified.Funding: This research did not receive any specific grant or financial support from public, commercial, or not-for profit funding agencies.Participant Consent: The authors confirm that Informed consent was obtained from all participants, and confidentiality was duly maintained.
Keywords: Khilāfa (Caliphate), Islamic political thought, Qur’anic worldview, political theology, South Asian Islamic thought